Resilience of rice (Oryza spp.) pollen germination and tube growth to temperature stress - Coast, Onoriode; Murdoch, Alistair J.; Ellis, Richard H.; Hay, Fiona R.; Jagadish, Krishna S.V. (Wiley, 2016)
Resilience of rice cropping systems to potential global climate change will partly depend on the temperature tolerance of pollen germination (PG) and tube growth (PTG). Pollen germination of high temperature‐susceptible Oryza glaberrima Steud. (cv. CG14) and Oryza sativa L. ssp. indica (cv. IR64) and high temperature‐tolerant O. sativa ssp. aus (cv. N22), was assessed on a 5.6–45.4 °C temperature gradient system. Mean maximum PG was 85% at 27 °C with 1488 μm PTG at 25 °C. The hypothesis that in each pollen grain, the minimum temperature requirements (Tn) and maximum temperature limits (Tx) for germination operate independently was accepted by comparing multiplicative and subtractive probability models. The maximum temperature limit for PG in 50% of grains (Tx(50)) was the lowest (29.8 °C) in IR64 compared with CG14 (34.3 °C) and N22 (35.6 °C). Standard deviation (sx) of Tx was also low in IR64 (2.3 °C) suggesting that the mechanism of IR64's susceptibility to high temperatures may relate to PG. Optimum germination temperatures and thermal times for 1 mm PTG were not linked to tolerating high temperatures at anthesis. However, the parameters Tx(50) and sx in the germination model define new pragmatic criteria for successful and resilient PG, preferable to the more traditional cardinal (maximum and minimum) temperatures.